Photopolymerizable Porous Polyorganophosphazenes Degradable Matrices for Tissue Engineering - Aigner, Tamara Bernadette; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2015)
Tamara Bernadette Aigner designed a set of biocompatible and biodegradable poly(organophosphazenes). In order to tailor their biological and chemical properties, she further modified these macromolecules by adding functional moieties via thiol-ene chemistry. The author used the same photochemistry for crosslinking to obtain a mechanically stable network. She further altered the degradation rate of the matrix as well as the mechanical properties by adding blending agents and created a porous matrix, which is necessary for cell invasion and communication, by a newly developed photocrosslinking particulate-leaching method. Thus, a modular hybrid system was established which is able to adapt to different microenvironments based upon tissue type. Contents Polyphosphazenes as Biocompatible and Biodegradable Polymers Functionalization and Crosslinking with Thiol-ene Chemistry Matrix Formation Using a Photocrosslinking Particulate-Leaching Technique Tailored Physical and Biochemical Properties by Blending Target Groups Researchers and students in the field of chemistry and biology with a focus on polymerchemistry and tissue engineering The Author Tamara Bernadette Aigner completed her master’s thesis in biological chemistry at Johannes Kepler University in Linz and South Bohemian University in České Budĕjovice.
Polyphosphazenes as Biocompatible and Biodegradable Polymers -- Functionalization and Crosslinking with Thiol-ene Chemistry -- Matrix Formation Using a Photocrosslinking Particulate-Leaching Technique -- Tailored Physical and Biochemical Properties by Blending.
Keywords: Biomaterials; Medicinal chemistry; Inorganic chemistry; Biomaterials; Medicinal Chemistry; Inorganic Chemistry